The sorcerer's shadow - Quinn, Jordan (Quinn, Jordan. Kingdom of Wrenly., 2017)
Prince Lucas, his friend Clara, and Ruskin the dragon travel with a team of knights to the forest of Trellis, where they discover that an evil sorcerer's shadow has cursed the land and only someone pure of heart and full of hope can save them.